Determinação de corantes sintéticos em bebidas isotônicas empregando extração em fase sólida dispersiva e HPLC-UV/Vis - Floriano, Luana (2016)
Sports drinks are specially formulated for people who are undertaking physical activity, being mainly composed by carbohydrates, electrolytes and vitamins. Synthetic dyes are food additives commonly used in sports drinks to improve their consumer characteristics and appearance. Besides the lower cost of production in relation to dyes of natural origin, synthetic colorants have several advantages such as high stability to light, oxygen and pH, color uniformity and low microbiological contamination. However some of these compounds cause adverse health effects (allergy, asthma, hyperactivity, thyroid tumors, etc.), especially when consumed in excess. Thus, their use is strictly controlled around the world. The present study aimed to develop a simple, fast and efficient method for the determination of the synthetic dyes tartrazine, sunset yellow, amaranth, ponceau 4R, indigo carmine and brilliant blue in sports drinks employing dispersive solid-phase extraction (d-SPE) and high eficiência liquid chromatography with ultraviolet/visible detection (HPLC-UV/Vis) In the extraction step, it was used 25 mg of the polymeric sorbent Oasis® HLB and the elution step was performed with metanol:ammonium hydroxide (95:5, v/v). Recovery results, evaluated at 2.0; 4.0 and 6.0 mg L-1, were between 76 and 108% with relative standard deviation (RSD) <18%. Method limits of detection and quantification were 0.6 and 2 mg L-1, respectively. The method was applied on 8 commercial samples of sports drinks and the results indicated that all studied samples presented dye levels in conformity with the Brazilian legislation. The proposed d-SPE method for the determinatios of 6 synthetic dyes in sports drinks using HPLC-UV/Vis shown to be rapid, effective and cheap, and can be applied in routine analysis.